1998
DOI: 10.1182/blood.v92.9.3226
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1 in Transgenic Mice Promotes Survival in a Spectrum of Hematopoietic Cell Types and Immortalization in the Myeloid Lineage

Abstract: Mcl-1 is a member of the Bcl-2 family that is expressed in early monocyte differentiation and that can promote viability on transfection into immature myeloid cells. However, the effects of Mcl-1 are generally short lived compared with those of Bcl-2 and are not obvious in some transfectants. To further explore the effects of this gene, mice were produced that expressed Mcl-1 as a transgene in hematolymphoid tissues. The Mcl-1 transgene was found to cause moderate viability enhancement in a wide range of hemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(42 citation statements)
references
References 55 publications
4
37
0
1
Order By: Relevance
“…Accordingly, the inhibition of this pathway may explain the efficacy of CXCR4 antagonists in this setting. In line with our observations, Mcl‐1 has been reported to mediate apoptosis resistance to fludarabine and rituximab in vivo (Zhou et al, 1998; Johnston et al , 2004; Pepper et al, 2008; Awan et al, 2009), and downregulation of Mcl‐1 by siRNA enhances RIT‐mediated apoptosis in vitro (Hussain et al , 2007).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Accordingly, the inhibition of this pathway may explain the efficacy of CXCR4 antagonists in this setting. In line with our observations, Mcl‐1 has been reported to mediate apoptosis resistance to fludarabine and rituximab in vivo (Zhou et al, 1998; Johnston et al , 2004; Pepper et al, 2008; Awan et al, 2009), and downregulation of Mcl‐1 by siRNA enhances RIT‐mediated apoptosis in vitro (Hussain et al , 2007).…”
Section: Discussionsupporting
confidence: 90%
“…We and others observed upregulation of the anti‐apoptotic Bcl‐2 family member Mcl‐1 upon stromal cell contact (Balakrishnan et al , 2009). The potential role of Mcl‐1 as an oncogene in lymphoid malignancies was confirmed in transgenic mouse models in which animals with deregulated expression of Mcl‐1 eventually developed widely disseminated B‐cell lymphoma (Zhou et al , 1998). Interestingly, in CLL, stromal cell contact also upregulates Akt activation (Edelmann et al , 2008), an effect abrogated by CXCR4 antagonists (Fig 1C).…”
Section: Discussionmentioning
confidence: 96%
“…Expression of MCL‐1 was also observed to be present and mostly stable throughout hematopoiesis, especially during B and T lymphocyte development from hematopoietic stem cells, which is followed by common lymphoid progenitor . This phenomenon was also supported by the data obtained from MCL‐1‐overexpressing transgenic mice, which demonstrated splenomegaly with increased hematopoiesis and increased leukocyte survival . More importantly for the subject of this review, different types of B‐cell lymphomas was also a consequence observed in these MCL‐1‐overexpressing transgenic mice .…”
Section: Discussionsupporting
confidence: 61%
“…Studies using transgenic and gene‐knockout mice have greatly illuminated the biological functions of Bcl‐2 family members. Demonstrating the role of the guardians, overexpression in lymphoid and other haemopoietic cells of Bcl‐2 (McDonnell et al , 1989; Strasser et al , 1990b, 1991a, 1991b; Sentman et al , 1991), Bcl‐x L (Grillot et al , 1995), Mcl‐1 (Zhou et al , 1998; Campbell et al , 2010) or A1 (Chuang et al , 2002) protects against diverse cytotoxic signals, both physiological (e.g. cytokine deprivation) or imposed (e.g.…”
Section: Physiological Functions Of Bcl‐2 Family Membersmentioning
confidence: 99%